Eksplorasi Efek Hidrasi Lotion Yang Diperkaya Dengan Ekstrak Clitoria Ternatea Pada Kulit Mus Musculus Yang Terpapar Sinar UV - Prabowo, Cheryl; Pribadi , Florence; Mellyanawati, Mellyanawati (Journal of Pharmaceutical and Sciences, 2026)
This study aimed to evaluate the effectiveness of a lotion enriched with butterfly pea flower extract (Clitoria ternatea) in improving skin hydration in mice (Mus musculus) exposed to ultraviolet (UV) light. Butterfly pea flower extract is known to contain anthocyanins and phenolic compounds, which act as antioxidants and are thought to maintain skin moisture. The study design used an experimental method. Mice were randomly allocated into five groups (n = 6 per group), consisting of a negative control group, a positive control group, and three treatment groups receiving butterfly pea flower extract lotion at concentrations of 0.5%, 1%, and 2%.  Skin hydration levels were measured using a Scalar Moisture Checker after five minutes of UV exposure. The results showed a significant difference in hydration levels between groups. The 1% butterfly pea flower extract lotion showed a significant increase in skin hydration compared to the negative control (p < 0.05), indicating its optimal moisturizing efficacy among the tested formulations. These findings indicate that butterfly pea flower extract has potential as an active ingredient in lotion formulations to improve hydration in skin damaged by UV light exposure. This study provides a scientific basis for the use of butterfly pea flower extract as a natural moisturizing agent.